Big promises, small gains: Domestic effects of human rights treaty ratification in the member states of the gulf cooperation council - Cali, Basak; Ghanea, Nazila; Jones, Benjamin (Human rights quarterly, 2016)
In recent years, the Gulf Cooperation Council (GCC) states have been increasingly willing to ratify United Nations human rights instruments. This article examines the underlying rationales for these ratifications and the limited range and drivers of subsequent domestic reforms post ratification. Drawing on both a quantitative analysis of engagement with the UN treaty bodies and Charter-based mechanisms in over 120 UN reports and qualitative interviews with over sixty-five government officials, members of civil society, National Human Rights Institutions, lawyers, and judges from all six states, this article argues that in the GCC states, UN human rights treaty ratification results from a desire to increase standing in the international community. Treaty ratification has limited effects driven by international socialization and cautious leadership preferences.
CRIS-Team Scopus Importer:2023-03-21